Legal grounds for justification of the legal status of the convicted as bearers of constitutional rights and freedoms - Albina Diakova (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право», 2023)
The article analyzes the legal grounds for substantiating the legal status of convicts as holders of constitutional rights and freedoms, as well as the need for a comprehensive analysis of this issue from the point of view of the science of constitutional law of Ukraine. After all, such an approach acts as an important and necessary doctrinal basis for comprehensive improvement of penitentiary legislation and the practice of its implementation. However, on the basis of the analysis of the achievements of modern legal doctrine, the fact is stated that such studies are clearly lacking. Instead, the main attention is paid to the study of the rights and freedoms of persons serving a sentence within the framework of other legal sciences. The thesis is proved that a look at the mentioned problem from the point of view of the science of constitutional law of Ukraine will allow to reveal those fundamental and most important aspects that cannot objectively be revealed within the scope of the study of other legal sciences. So, in particular, it will make it possible to look at the existing rights, freedoms and duties of convicts critically and from the perspective of high constitutional standards in this area, as well as to form a scientific basis for the fundamental reform of the legal status of convicts and the internal organizational mechanisms for ensuring it.